Lego Star Wars the visual dictionary - Beecroft, Simon; Beckett, Jeremy; DK Publishing, Inc. (New York, N.Y. : DK Pub., 2009)
Darth Vader, Boba Fett, Yoda, Luke Skywalker, and more are brought to life with dozens of little-known facts and hundreds of photos, as are accessories, vehicles, weapons, and even the Death Star. Learn about the history, manufacture, and construction of the minifigures of the "Star Wars" galaxy, and come away a LEGOʼ Jedi Master.
"With exclusive minifigure."
7+.
Keywords: Models and modelmaking -- Juvenile literature; LEGO toys -- Juvenile literature; Star Wars films -- Juvenile literature